FAMILY COMMUNICATION PORTRAIT IN THE MIDDLE OF SOCIAL CHANGE IN BOGOR - Firdanianty Pramono; Djuara P Lubis; Herien Puspitawati; Djoko Susanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
The advancement of information and communication technology have a positive and negative impacts on family ties and values. These developments also change the order of family life as the smallest unit in society. Family interaction and communication also change along with social change in society. The purposes of this study are: first, to explore the topics of conversation and interaction of adolescents with their families. Second, to depict four types of communication between adolescents and their families. This study was conducted for 6 months in 6 high schools in Bogor with qualitative methods. Data were obtained through focus group discussion (FGD) in each high school with a total of 12 FGDs. The number of informants involved in the FGD were 60 students aged 15-18 years old. The FGD results show that most of theadolescents shared their personal problems to peers than to parents. The topics presented by adolescents to parents included events at school (lessons, teachers, friends), television shows, ideals, sports, and politics. Some adolescents who had close relationships with parents did not hesitate to share their personal problems and interests of the opposite sex to their parents. Adolescents who had closeness to parents tend to be more open and were able to control their emotions. The findings of this study are expected to provide inputto the family as well as to improve the quality of communication between adolescents and parents.